(untitled) (Minerva, 2018)
Poet and polygraph Gabriel Bocángel (Madrid, 1603-1658) wrote his Quintiliano respondido (Answer to Quintilian) in 1647, a work where he responds to Declamatio maior 8, falsely ascribed to Quintilian. The ancient piece, a controversia, presents the fictive speech against a father who has allowed for the murder and dissection of one of his twin sons. That was, one doctor alleged, the only way to save the other twin’s life from the apparently incurable disease both brothers were suffering. Bocángel addresses his composition to the duke of Sessa, whose patronage he was searching for, and chooses his subject out of his interest towards medicine. Bocángel deals with the Latin text by adopting the opposite position and displays his rhetorical ability, refuting one by one the arguments in the original. With the help of the same resources as his model (prosopopoeia, apostrophe, evidentia, ethopoeia) he composes a text which shows the key role of rhetoric at the time, but that at the same time addresses a limited readership, as it circulated only in manuscript form until it was edited in 2000.